Clinical Characteristics, Life Adversities and Personality Traits in Monozygotic Twins With, at Risk of and Without Affective Disorders - Ottesen, Ninja M.; Meluken, Iselin; Scheike, Thomas; Kessing, Lars V.; Miskowiak, Kamilla W.; Vinberg, Maj (Frontiers in Psychiatry, 2018)
Background: Affective disorders have a long-term impact on psychiatric health and are caused by multiple interacting factors including familial risk, childhood adversity, life events and personality traits. Methods: In this study, monozygotic twins (MZ) at familial risk (indexed by affective disorder in their co-twin; high-risk group), affected MZ twins (indexed by a diagnosis with affective disorder) and MZ twins with no family history of affective disorder (low-risk group) were identified through cross-linking of nation-wide Danish registers. In total, 204 MZ twins were included and psychopathology, personality traits and life adversity were evaluated by semi-structured interviews and questionnaires. Results: Affected MZ twins presented with more subclinical affective symptoms and were functionally impaired as evidenced by higher unemployment rates and reduced functional status. The affected and the high-risk groups reported more childhood adversity and had experienced more stressful life events than the low-risk group. A direct comparison within the discordant twin pairs showed that the high-risk twins presented fewer affective symptoms, better functional status, more extraversion and lower neuroticism scores than their affected co-twins although they had equal levels of life adversity as their affected co-twins Conclusion: These findings add to the evidence indicating that patients experience higher neuroticism, persistent subclinical symptoms and reduced socio-occupational function after affective episodes. Additionally, neuroticism and extraversion seem capable of moderating the sensitivity to exposure from the environment.